Intervention of Combined Breast Care and Oxytocin Massage on Improving Breast Milk Flow in Postpartum Mothers - Saudah, Noer; Yahya, Vivi Aleyda; Dewi, Catur Prasastia Lukita (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Breast milk (BM) serves as the primary source of nutrition for infants from birth until six months of age. However, during the early postpartum period, BM production is often limited, necessitating non-pharmacological interventions such as a combination of breast care and oxytocin massage to stimulate prolactin and oxytocin hormones. The purposed this study is Intervention of Combined Breast Care and Oxytocin Massage to Improve Breast Milk Flow in Postpartum Mothers. This study employed a pre-experimental design with a one-group pre-test post-test approach. A total of 45 post-cesarean section mothers who met the inclusion criteria were selected using consecutive sampling. The intervention, consisting of breast care combined with oxytocin massage, was administered twice daily for seven days. Research instruments included a breast milk adequacy questionnaire and an observation sheet. Data were analyzed using the Wilcoxon Signed Ranks Test via SPSS version 26. Before the intervention, 41 respondents (91.1%) experienced inadequate BM flow, while 4 respondents (8.9%) had adequate BM flow. After the intervention, all respondents (100%) achieved adequate BM flow. The Wilcoxon test yielded a p-value of 0.000 (p<0.05), indicating a significant effect. The combination of breast care and oxytocin massage was proven effective in improving BM adequacy among postpartum mothers and can be recommended as a non-pharmacological approach to support exclusive breastfeeding programs.